LEGAL PROTECTION AND WELFARE IN EDUCATION: A POST-PANDEMIC RECOVERY PERSPECTIVE ON IMPLEMENTING LAW NO. 14 OF 2005 - Wartoyo, Franciscus Xaverius; Prasetyo, Teguh (UNISSULA, 2023)
Legal protection for teachers and lecturers in the post-COVID-19 pandemic period needs to be pursued, because it is part of improving their welfare in addition to safety in every activity and task. As referred to in article 14 paragraph (1) point e